Склад населення, похованого на могильнику скіфської доби біля м. Світловодськ (за матеріалами краніології) - Круц, С.І.; Рудич, Т.О. (Археологія і давня історія України, 2021)
У статті подається попередня інформація стосовно краніологічного матеріалу з розкопок скіфського могильника біля м. Світловодськ та аналізується склад його населення в колі скіфських груп
з території України. The anthropological composition of the population
buried at the cemetery of the Scythian Age near Svitlovodsk
city (Kirovograd region) is analyzed in the paper.
The burial ground is located on the border of the
Forest-Steppe and Steppe Zones of the Right Bank of
the Dnieper. The anthropological material under study
comes from cemetery without mounds. Archaeologists
date the main massif of burials to the 4th century BC.
The anthropological composition of the population that
was buried at this burial ground was not homogenous.
The male series of skulls is characterized by a long,
medium-wide, high, dolichocranic skull. The face is of
medium size, it is mesognathic. The horizontal profile of
the face at the upper level is medium, but with a tendency
to the sharp; at the middle level, the face is strongly
profiled. The orbital and nasal indexes are medium. The
bones of the nose are moderately protruding.
The average characteristics of the male population
fit into the range of variations of the Scythian series.
The male series belongs morphologically and statistically
to the circle of the steppe Scythian groups. The
male group from the burial ground near the city of
Svitlovodsk is close to the series from the Nikolaevka
burial ground on the Dnister River, the group of skulls
from the burial mounds near the village of Shirokoe
(Left Bank of the Dnieper River), the group of skulls
from the burial mounds near the village of Vyshchetarassivka,
a series of skulls from the Mykhailivka
burial ground.
Of the forest-steppe series, only the combined group
of skulls from the Trypillya region is somewhat close
to it.
All these statistically and morphologically similar
groups originate from different territories. This illustrates
the specifics of the settlement and demonstrates
the mobility of the Scythian groups.
The female series from the burial ground is characterized
by a long, narrow, medium-high skull, mesocranic
in shape. The size of the face is small, it is mesognathic.
The horizontal profile of the face at the upper
level is moderate, at the zygomaxilar level it belongs to
the category of sharp, but with a tendency to moderate.
The orbital index is medium, the nasal index belongs to
the large category. The bones of the nose are medium
protruding.
The female series from Svitlovodsk burial ground
turns out to be the most gracile among the Scythian series
in Ukraine. For this reason, it differs significantly
from the entire massif of the steppe Scythian series.
The closest to the Svitlovodsk series is a group from
mounds near Nikopol.